Crimean-Congo hemorrhagic fever and its relationship with climate factors in southeast Iran: a 13-year experience - Hossein Ansari; Babak Shahbaz; Shahrokh Izadi; Mohammad Zeinali; Seyyed Mehdi Tabatabaee; Mahmood Mahmoodi; Kourosh Holakouie Naieni; Mohammad Ali Mansournia (Journal of Infection in Developing Countries)
Introduction: Crimean-Congo hemorrhagic fever (CCHF) is endemic in southeast Iran. In this study we present the epidemiological features of CCHF and its relationship with climate factors in over a 13-year span. Methodology: Surveillance system data of CCHF from 2000 to 2012 were obtained from the Province Health Centre of Zahedan University of Medical Sciences in southeast Iran. The climate data were obtained from the climate organization. The seasonal auto-regression integrated moving average (SARIMA) model was used for time series analysis to produce a model as applicable as possible in predicting the variations in the occurrence of the disease. Results: Between 2000 and 2012, 647 confirmed CCHF cases were reported from Sistan-va-Baluchistan province. The total case fatality rate was about 10.0%. Climate variables including mean temperature (°C), accumulated rainfall (mm), and maximum relative humidity (%) were significantly correlated with monthly incidence of CCHF (p <0.05). There was no clear pattern of decline in the reported number of cases within the study’s time span. The first spike in the number of CCHF cases in Iran occurred after the first surge of the disease in Pakistan. Conclusions: This study shows the potential of climate indicators as predictive factors in modeling the occurrence of CCHF, even though it has to be appreciated whether there is any need for a practically applicable model. There are also other factors, such as entomological indicators and virological finding that must be considered.